Défis, limites et promesses d’une sémantique historique en études ottomanes - Erdal Kaynar (European Journal of Turkish Studies)
This article discusses the uses of conceptual history and historical semantics for Ottoman studies. It cautions against scientific and political pitfalls that may arise from a simplistic and uncritical adaptation of an historiographical trend and invites for a reflective approach to the study of Ottoman socio-political language primarily of the 19th/20th centuries. The language of the Ottoman Empire differs fundamentally as an object of historical study from Western European cases, where studies on conceptual history have proliferated, which poses a real challenge to historical semantics in Ottoman studies. However, its specificities can and partly already have given rise to highly reflective methods in the study of language change. The article follows ideas of semantic fields or world fields put forward in particular since the 1980s to discuss particularities and possibilities of historical semantics in Ottoman studies beyond classical methods associated with conceptual history. It argues that, despite all shortcomings, working on the Ottoman socio-political language can be a unique tool beyond the dichotomy of social and intellectual history to study a level of historical experience defined by mentalities, ideology, and the unconscious.